2023
DOI: 10.1021/acsami.2c19272
|View full text |Cite
|
Sign up to set email alerts
|

Development of Deep Potentials of Molten MgCl2–NaCl and MgCl2–KCl Salts Driven by Machine Learning

Abstract: Molten MgCl 2 -based chlorides have emerged as potential thermal storage and heat transfer materials due to high thermal stabilities and lower costs. In this work, deep potential molecular dynamics (DPMD) simulations by a method combination of the first principle, classical molecular dynamics, and machine learning are performed to systemically study the relationships of structures and thermophysical properties of molten MgCl 2 − NaCl (MN) and MgCl 2 −KCl (MK) eutectic salts at the temperature range of 800−1000… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…Then, the small time-length of MLPMD further causes inadequate sampling, thus making the model evolution too slow in the first few rounds (Figure c). The issue could be addressed by using data augmentation to increase the diversity of initial training data, e.g., perturbing DFT-relaxed structures, collecting DFT-labeled data from MD simulations with different temperatures, pressures, unit cells, thermodynamic ensembles, etc., see refs , and . However, it needs extra computational costs.…”
Section: Resultsmentioning
confidence: 99%
“…Then, the small time-length of MLPMD further causes inadequate sampling, thus making the model evolution too slow in the first few rounds (Figure c). The issue could be addressed by using data augmentation to increase the diversity of initial training data, e.g., perturbing DFT-relaxed structures, collecting DFT-labeled data from MD simulations with different temperatures, pressures, unit cells, thermodynamic ensembles, etc., see refs , and . However, it needs extra computational costs.…”
Section: Resultsmentioning
confidence: 99%
“…However, previous studies on molten salt NNPs have shown that the NNP’s performance becomes less sensitive to changes in the hyper-parameters once a certain threshold is reached. ,, , These include but are not limited to the size of the hidden layers for the embedding and hidden networks, the prefactor values for the average atomic energy and forces, the r c and r cs values, and the maximum number of neighbors for each atom. For instance, in the investigation of NNPs for molten MgCl 2 –NaCl and MgCl 2 –KCl salts by Xu et al., it was observed that the RMSE values for average atomic energies and forces did not experience significant changes with larger neural networks, greater cutoffs for atomic interactions, or a larger number of maximum neighboring atoms. Considering this, along with the fact that our training protocols in this study adequately reproduce various experimental properties (as discussed in Section ), further fine-tuning of the NN hyperparameters was not explored, and the selected hyperparameters were proved to be sufficient for achieving accurate results.…”
Section: Methodsmentioning
confidence: 99%
“…Xu et al studied two eutectic chloride molten salts, MgCl 2 −NaCl (MN) and MgCl 2 −KCl (MK). 32 Compared to individual salts, the coordination numbers of Mg−Cl, Na−Cl, and K−Cl in molten MN and MK were found to be higher, indicating that cations have a stronger ability to trap Cl − in the molten mixtures. These researches showed that DPMD not only has the same precision as AIMD in structural prediction but also can simulate with faster calculation speed and larger calculation dimension.…”
Section: Introductionmentioning
confidence: 96%
“…The basic transport properties such as density, self-diffusion coefficient, shear viscosity, and conductivity were in good agreement with experimental data. Xu et al studied two eutectic chloride molten salts, MgCl 2 –NaCl (MN) and MgCl 2 –KCl (MK) . Compared to individual salts, the coordination numbers of Mg–Cl, Na–Cl, and K–Cl in molten MN and MK were found to be higher, indicating that cations have a stronger ability to trap Cl – in the molten mixtures.…”
Section: Introductionmentioning
confidence: 99%